Formulation of capsule preparations with variations in aerosil concentration on the results of preparation evaluation - Arif Wijayanto; Juvita Herdianty (Strada Journal of Pharmacy, 2020)
Capsules can be defined as a solid dosage form, where one or more types of drugs and/or other inert ingredients are contained in a shell or small container that can dissolve in water (Ansel 2005). Gelatin is a suitable material for making capsule shells because it is edible and soluble, forms a strong, thin-layered shell and changes from solution to gel form slightly above ambient temperature. Gelatin immediately dissolves in water at body temperature and does not dissolve if the temperature drops below 30°C (Agoes, 2008). Based on the test results, the disintegration time for F1 capsules is 2.12 minutes; F2 is 2.21 minutes; and F3, namely 2.27 minutes. These three formulas meet the requirements, namely not less or equal to 15 minutes. Based on the test results, F1 3.44 seconds, F2 3.76 seconds, F3 3.24 seconds, the flow speed of these three formulas meets the flow speed requirements, namely flow speed ≥ 10 g/second. The flow speed of the three formulas is in the good category, namely 2-10 g/sec which is said to be very good while it is said to be good. The flow speed is good because Aerosil has a very small and fine particle size. Apart from being an absorbent, aerosols are also able to improve flow properties by reducing friction between particles and by averaging test results from angles of repose F1 45°, F2 43° and F3 53°. In the weight uniformity test at F 1,2,3 it does not meet the requirements for factors that influence weight uniformity, namely lack of accuracy, different drug weights due to uneven distribution.